Ending the Journey of Suffering - Avny, Ohad; Grin, Batya (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2025)
The relationship between a family physician and their patients often spans many years. The primary care physician guides the patient through medical procedures and complicated decisions. Even if the physician is not the doctor making all the decisions or tailoring the treatment plan, they are often viewed by the patient as the case manager. The importance of this role is particularly evident in the geriatric population, where the challenge lies in balancing the benefits of treating complex diseases against the potential impact on the patient’s quality of life. The physician’s ability to navigate such complex issues stems not only from their professional capabilities but also from the personal relationship between them and the patient. While friendship that tends to develop over the years between a doctor and their patient can often aid the doctor in such decision-making process, occasionally such a relationship can be a pitfall. A doctor-patient relationship grounded in compassion optimizes the decision-making process to better meet the patient’s needs. That being said, it is also understood that crossing the bounds of the traditional doctor-patient relationship can present significant moral dilemmas. This story illustrates the relationship between a family physician and an elderly patient that spans over two decades. Their friendship, partially due to a prior acquaintance, influences many of their interactions, culminating in the patient’s tragic death. This text explores the sometimes-conflicting obligations of friendship versus professionalism and the ethical dilemma in of those intersecting responsibilities.